Observation of charmonium pairs produced exclusively in $pp$ collisions - Aaij, R; Adeva, B; Adinolfi, M; Affolder, A; Ajaltouni, Z; Akar, S; Albrecht, J; Alessio, F; Alexander, M; Ali, S; Alkhazov, G; Cartelle, P; et al. (Institute of Physics Publishing, 2014)
A search is performed for the central exclusive production of pairs of charmonia produced in proton-proton collisions. Using data corresponding to an integrated luminosity of $3{\rm\ fb}^{-1}$ collected at centre-of-mass energies of 7 and 8 TeV, $J/\psi J/\psi$ and $J/\psi\psi(2S)$ pairs are observed, which have been produced in the absence of any other activity inside the LHCb acceptance that is sensitive to charged particles in the pseudorapidity ranges $(-3.5,-1.5)$ and $(1.5,5.0)$. Searches are also performed for pairs of P-wave charmonia and limits are set on their production. The cross-sections for these processes, where the dimeson system has a rapidity between 2.0 and 4.5, are measured to be $$ \begin{array}{rl} \sigma^{J/\psi J/\psi} and= 58\pm10{(\rm stat)} \pm 6{(\rm syst)} {\rm\ pb} , \\ \sigma^{J/\psi\psi(2S)} and= 63 ^{+27}_{-18}{(\rm stat)}\pm 10{(\rm syst)} {\rm\ pb} , \\ \sigma^{\psi(2S)\psi(2S)} and< 237 {\rm\ pb}, \\ \sigma^{\chi_{c0}\chi_{c0}} and< 69 {\rm\ nb}, \\ \sigma^{\chi_{c1}\chi_{c1}} and< 45 {\rm\ pb}, \\ \sigma^{\chi_{c2}\chi_{c2}} and< 141 {\rm\ pb}, \\ \end{array} $$ where the upper limits are set at the 90% confidence level. The measured $J/\psi J/\psi$ and $J/\psi\psi(2S)$ cross-sections are consistent with theoretical expectations.